STUDI LITERATUR TENTANG IMPLIKASI POLIGAMI TERHADAP EKONOMI KELUARGA - Tamam, Usef Muhamad (LPPM STAI Al-Azhary Cianjur, 2025)
This study aims to analyze the implications of polygamy on the economic conditions of families based on current and relevant literature. Employing a qualitative approach through library research, the author examines the concepts and principles of polygamy in Islam, legal provisions on marriage, and financial management practices in polygamous households. The analysis focuses on the allocation of financial support, the management of basic and secondary needs, long-term financial planning, and the role of financial literacy in supporting household resilience and harmony. The findings indicate that careful and transparent financial planning, equitable distribution of responsibilities, and open communication between spouses are crucial to minimizing conflicts and inequalities in polygamous families. Moreover, financial literacy plays a significant role in ensuring that the needs of all family members are met proportionally and sustainably. With proper financial management and adherence to principles of justice, polygamy has the potential to promote well-being and strengthen family stability. Conversely, without adequate planning and oversight, polygamy may lead to tension, dissatisfaction, and a decline in the quality of family life.